Resposta :
x¹ = -4
x² = 7
2x² - 6x – 56 = 0 (÷2)
x²-3x-28 = 0
∆ = b²-4ac
∆ = (-3)²-4(1)(-28)
∆ = 9+112
∆ = 121
-b+-√∆/2a
-(-3)+-√121/2(1)
3+-11/2
x¹ = 3-11/2 = -8/2 = -4
x² = 3+11/2 = 14/2 = 7
❤️ Espero ter ajudado ❤️
01/09
![Ver imagem GLAUCIACKLESSPAA44T](https://pt-static.z-dn.net/files/de8/b63e2482f650382aec03b0e4395ead77.jpg)
2x² - 6x – 56 = 0 (÷2)
x²-3x-28 = 0
∆ = b²-4ac
∆ = (-3)²-4(1)(-28)
∆ = 9+112
∆ = 121
-b+-√∆/2a
-(-3)+-√121/2(1)
3+-11/2
x¹ = 3-11/2 = -8/2 = -4
x² = 3+11/2 = 14/2 = 7
01/09